2012
DOI: 10.1159/000342215
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Bacterial Type and Antibiotic Sensitivity with Maternal Antibiotic Exposure in Early-Onset Neonatal Sepsis

Abstract: Background: Antibiotic administration during pregnancy as group B Streptococcus prophylaxis or as treatment of maternal conditions has become widespread. Objective: To assess whether bacterial type and antibiotic resistance in early-onset neonatal sepsis are associated with maternal antibiotic use. Methods: All positive blood and/or cerebrospinal fluid cultures (case-only study) and respective antibiotic sensitivities from newborns delivered in Shaare Zedek Medical Center, Jerusalem, Israel, between 01/01/1997… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…Previous studies demonstrated the importance of considering these aspects of antenatal antimicrobial exposure. 7,16,19 Comprehensive antimicrobial resistance profiles were not captured within the dataset. Ampicillin resistance secondary to narrow spectrum beta-lactamases does not reliably predict resistance to first-generation cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the importance of considering these aspects of antenatal antimicrobial exposure. 7,16,19 Comprehensive antimicrobial resistance profiles were not captured within the dataset. Ampicillin resistance secondary to narrow spectrum beta-lactamases does not reliably predict resistance to first-generation cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…Host factors could specifically predispose a newborn to infections by antibiotic-resistant GNB. Several studies have reported an increased risk of neonatal infections by antibiotic-resistant pathogens with intrapartum exposure to ampicillin [34][35][36][37][38]. Penicillins are typically the recommended intrapartum antibiotic given to women with group B Streptococci (GBS) colonization to reduce the risk of early neonatal sepsis [39].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we found that antibiotic use during delivery and artificial rupture of the membrane were statistically significant higher among the carrier neonates compared to all non-carrier neonates and compared to non-carrier neonates born to a carrier mother. ESBL and MRSA carriage rates among newborns were previously associated with antibiotic use [14,[40][41][42]. Antibiotic use during delivery may contribute to the development or survival of resistant bacteria in the pregnant mother that may transmit to the neonate while passing through the birth canal.…”
Section: Risk Factors For Neonatal Colonizationmentioning
confidence: 99%